Smart dashboards for smart city - A platform to engage with citizen - Vasudavan H.; Balakrishnan S.; Jing T.; Vijay K.; Gunasekaran S.S. (American Scientific Publishers, 2023)
Smart City is the term composed for a city that aggressively balances itself through ICT based urban solutions and solving multiple problems faced by the ever complex urban lifestyle. Big data analytics is one of the best innovation to process extracted data from this Internet of Things (IoT) Ecosystem of the smart city. In this ecosystem, the communication and engagement with the city residents are very important. The smart dashboard is a hyper connected platform to effectively project the smart city dimension's performance to stakeholder and residents. Thus creating an instant engagement with the citizens. Although most of the smart cities has been computing all the data gathered in the city using the most sophisticated data analytics tools, it has not effectively interfaced it to the benefit of city residents. A Smart Dashboard is seen as an enabler to the smart city dimensions but many of the current smart dashboards are still elusive and faces many challenges. There will be discussions about the importance of smart dashboard, a list of key indicators and the challenges to implementing this dashboard. 2019 American Scientific Publishers.